In a ‘Real-World’, Clinic-Based Community Setting, Sorafenib Dose of 400 mg/day is as Effective as Standard Dose of 800 mg/day in Patients with Advanced Hepatocellular Carcimona, with Better Tolerance and Similar Survival - Alexandra Shingina; Al Moutaz Hashim; Mazhar Haque; Michael Suen; Eric M Yoshida; Sharlene Gill; Fergal Donnellan; Alan A Weiss (Canadian Journal of Gastroenterology)
BACKGROUND: Sorafenib, an oral multityrosine kinase inhibitor, has been approved for treatment of unresectable hepatocellular carcinoma (HCC). British Columbia (BC) was the first province in Canada to provide drug coverage for sorafenib.